EMBRYONIC AND LARVAL DEVELOPMENT OF A RED STRAIN OF THE EGYPTIAN AFRICAN CATFISH (Clarias gariepinus Burchell, 1822) - Bambang Iswanto; Imron Imron; Rommy Suprapto; Huria Marnis (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2015)
Egyptian African catfish is one of several African catfish (Clarias gariepinus) strains introduced to Indonesia. Several breeding activities using that strain in Sukamandi resulted in some individuals with redish-yellow body colour (a red strain). Biological informations related to aquacultural aspects of that red strain were still scarce. The present study aimed to elucidate the embryonic and larval developments of the red strain compared to those of the black (normal coloured) one, using the progenies obtained from artificial spawning of each red and black coloured brooders. Results of the present study revealed that embryonic developments of the red and black strains were similar. Their larval development were also quite similar, however, both larvae could be distinguished based on the pigmentation. The red strain larvae were golden-red-yellowish in colour, while the black strain larvae were greyish covered with dense melanophores. Total length of the red strain larvae tended to be lower than those of the black strain.